Strengthening and Utilizing Original Tanimbar Woven Fabric as a Form of Preservation of Traditional Cultural Expression - Balik, Agustina; Hetharie, Yosia (Faculty of Law, Universitas Pattimura, 2022)
Introduction: The strengthening, utilization and preservation of EBT as an object of intellectual property rights produced by indigenous peoples or traditional communities is an interesting issue to study, one of which is the Tanimbar Weaving Fabric which is a form of intellectual work of the Tanimbar community.Purposes of the Research: The purpose of this study is to find out what the philosophical meaning and value of Tanimbar woven fabrics are as a form of traditional cultural expression and how the forms of strengthening and utilization of Tanimbar woven fabrics are as traditional cultural expressions.Methods of the Research: The research method used is normative legal research, using a statutory approach and a conceptual approach by examining various legal rules which are then linked to the reality that occurs in society. The legal materials used in this study are primary legal materials in the form of Copyright Law, while secondary legal materials in the form of books, legal journals related to the issues studied. The technique of collecting legal materials is done through a literature study that has relevance to this research. The legal materials collected were analyzed using qualitative analysis techniques to answer the problems in this research.Results of the Research: The original Tanimbar woven fabric has philosophical meaning and value for the Tanimbar community through the woven fabric motif. Each of these Tanimbar woven motifs has deep philosophical meanings and values regarding the life of the people and the environment of the Tanimbar people. Strengthening and Utilization of Tanimbar's original woven fabrics spun from cotton threads is increasingly being eroded by technological developments. The Tanimbar people no longer weave using cotton but have replaced it with shop yarn. In fact, the cultural heritage of Tanimbar woven fabrics inherited from their ancestors is the spinning of cotton threads, the results of which are very unique, have high economic value and are sought after by tourists and collectors of traditional fabrics. The government of the Tanimbar Islands Regency has not been able to provide protection, strengthening and utilization of the original Tanimbar woven fabrics.